A participação dos comitês de bacias hidrográficas na gestão dos recursos hídricos do Estado do Ceará: avanços, limites e desafios - Teixeira, Vânia Maria Simões Rodrigues (2006)
About 90% of the territory of the state of Ceará has a semi-arid region, where the water necessity as vital and economic resource has became more problematic, furthermore, it has, 70% of its territory formed by crystalline rocks, or either, reduced in groundwater. Another determinative factor is that the State does not possess perennial rivers, all are intermittent and the rainy period is concentrated in four months. These factors impose that the water is accumulated in reservoirs to guarantee offers of water for the diverse uses. In the water for the diverse uses. In the Ceará, the years of 1919-1931, they are characterized for investments of federal resources for the construction of great workmanships of combat to the droughts. However, the governmental actions had always prioritized the construction of dams, perforation of wells, and implantation of irrigation projects, without any cooperation with the diverse economic and social sectors, as well as without a planning that guaranteed the localization strategy of these dams with regard to the necessities of population supplying. The ownership of the water always was used as a source of economic power; it was always tied for many years to the private property. From the Constitution of 1988, the water was considered as a patrimony public. The lived current phase in the Ceará, it had started in the decade of eighty with the creation of the State Counsel of Water Resources and the accomplishment of Plan Zero of Water Resources. This current phase was consolidated, with the creation of the Secretariat of the Water Resources by the elaboration of the State Plan of water Resources, the contract signature of financings with the World Bank, the promulgation of Law Nº 11.996 /92 that it defined the Politics of the Water Resources and instituted the State System of Management of the Resources, and the creation of the Company of Management of the Water Resources - COGERH. The demand for the various water uses in the state of the Ceará has succeeded an increasing movement of participation of the population in the management of this resource. The decentralization if makes necessary, with the objective of legitimize and to fortify the organizations of the users in their respective basins or a hydrographic basin, through a process of co- responsibility of the diverse involved segments in the decisions of the Politics of the water Resources, to assure its utilization and preservation, in amount and quality, for the current and future generations. Since 1994, the COGERH comes developing an intense and significant work of mobilization and qualification of 17 the society for the management of waters, in the scopes of strategically dams, towns, perennial valleys, and hydrographical basins